Testing for Credibility Effects - Agenor, Pierre-Richard (IMF Working Papers; Working Paper, 1991)
This paper examines some recent techniques designed to draw inferences about the credibility of changes in macroeconomic policy regimes. An alternative two-step approach, based on the decomposition between permanent and transitory components of a "credibility variable" is proposed. The methodology is then used to test for the existence of a credibility effect in the Cruzado stabilization plan implemented in Brazil in 1986.